#Nicotineaddiction on TikTok: A quantitative content analysis of top-viewed posts - Kristy L. Marynak; Meagan O. Robichaud; Tyler Puryear; Ryan D. Kennedy; Meghan B. Moran (Tobacco Induced Diseases, 2022)
Introduction TikTok, the video-sharing app popular among youth, is a source of user-generated content about nicotine addiction with the potential to endorse or deter nicotine use among young viewers. We systematically analyzed content and themes of TikTok posts tagged #nicotineaddiction.